Media based education and motivation through phrasing: can they affect climate change willingness? - Tsamopoulos, Konstantinos; Marini, Kalliopi; Τσαμόπουλος, Κωνσταντίνος; Μαρίνη, Καλλιόπη (2023)
In the field of environmental communication, short and memorable phrases are often used to convey a message, either in the form of assertive commands or in suggestions. In this article, we are discussing the effects that a video can cause on the willingness of the subjects to adopt proenvironmental behaviors, as well as the effects of assertive and non-assertive slogans on motivation in this area. The sample of the research consisted of 103 students studying in the School of Environment at the University of the Aegean. The results were calculated by measuring how each student perceives the importance of his/her actions related to environmental protection, by answering a questionnaire about their daily habits; how they contribute to climate change and whether they are willing to change their behavior, before and after viewing an educational video about climate change. The video used was the winner of the Film4Climate competition of 2016. After the video, the subjects were asked to answer again knowledge and attitude questions to measure the changes that occurred. Then, they were asked to choose 1 out of 3 possible options regarding the type of a slogan for the video. The first slogan was assertive, the second was non assertive and the third option stated that the language form is irrelevant/the video alone would suffice. The key implication of the findings is that the video use is a great tool for environmental communication since it affects not only the knowledge of the subjects, but also their possible intentions to change their behavior too. The video has an effect on both knowledge, but also a large effect in their intentions to partake in environmental decision making. It was also observed that women were influenced more than men. The present research confirms the existing research and emphasizes the use of media on environmental education and communication.